Cutting-edge developments in plastic biodegradation and upcycling via engineering approaches - Zeinab Rezaei; Amir Soleimani Dinani; Hamid Moghimi (Metabolic Engineering Communications)
The increasing use of plastics has resulted in the production of high quantities of plastic waste that pose a serious risk to the environment. The upcycling of plastics into value-added products offers a potential solution for resolving the plastics environmental crisis. Recently, various microorganisms and their enzymes have been identified for their ability to degrade plastics effectively. Furthermore, many investigations have revealed the application of plastic monomers as carbon sources for bio-upcycling to generate valuable materials such as biosurfactants, bioplastics, and biochemicals. With the advancement in the fields of synthetic biology and metabolic engineering, the construction of high-performance microbes and enzymes for plastic removal and bio-upcycling can be achieved. Plastic valorization can be optimized by improving uptake and conversion efficiency, engineering transporters and enzymes, metabolic pathway reconstruction, and also using a chemo-biological hybrid approach. This review focuses on engineering approaches for enhancing plastic removal and the methods of depolymerization and upcycling processes of various microplastics. Additionally, the major challenges and future perspectives for facilitating the development of a sustainable circular plastic economy are highlighted.